2018
DOI: 10.1002/hep.30102
|View full text |Cite
|
Sign up to set email alerts
|

The Long Noncoding RNA Cancer Susceptibility 9 and RNA Binding Protein Heterogeneous Nuclear Ribonucleoprotein L Form a Complex and Coregulate Genes Linked to AKT Signaling

Abstract: The identification of viability-associated long noncoding RNAs (lncRNAs) might be a promising rationale for new therapeutic approaches in liver cancer. Here, we applied an RNA interference screening approach in hepatocellular carcinoma (HCC) cell lines to find viability-associated lncRNAs. Among the multiple identified lncRNAs with a significant impact on HCC cell viability, we selected cancer susceptibility 9 (CASC9) due to the strength of its phenotype, expression, and up-regulation in HCC versus normal live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 48 publications
4
92
1
Order By: Relevance
“…The authors identified and studied in molecular detail a prominent cytoplasmic lncRNA, CASC9 (cancer susceptibility candidate 9), which was preferentially abundant in HCC compared with normal liver. CASC9 had recently been shown to promote tumorigenesis in the esophagus, stomach, lung, and nasopharynx; in keeping with these findings, CASC9 was also significantly induced in HCCs and correlated inversely with patient survival . Moreover, a series of loss‐of‐function studies revealed that higher expression of CASC9 was strongly associated with major phenotypes observed in liver tumorigenesis, such as excessive proliferation and loss of susceptibility to apoptosis.…”
contrasting
confidence: 58%
See 4 more Smart Citations
“…The authors identified and studied in molecular detail a prominent cytoplasmic lncRNA, CASC9 (cancer susceptibility candidate 9), which was preferentially abundant in HCC compared with normal liver. CASC9 had recently been shown to promote tumorigenesis in the esophagus, stomach, lung, and nasopharynx; in keeping with these findings, CASC9 was also significantly induced in HCCs and correlated inversely with patient survival . Moreover, a series of loss‐of‐function studies revealed that higher expression of CASC9 was strongly associated with major phenotypes observed in liver tumorigenesis, such as excessive proliferation and loss of susceptibility to apoptosis.…”
contrasting
confidence: 58%
“…In this issue of Hepatology, Klingenberg et al (5) report a comprehensive collection of viability-associated lncRNAs in HCC. The authors identified and studied in molecular detail a prominent cytoplasmic lncRNA, CASC9 (cancer susceptibility candidate 9), which was preferentially abundant in HCC compared with normal liver.…”
Section: See Article On Page 1817mentioning
confidence: 99%
See 3 more Smart Citations